De nouvelles propositions de l'UE concernant le transport des animaux vivants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
La Commission européenne a adopté le 16 juillet 2003...